PENGARUH PEMBERIAN AIR KELAPA TERHADAP KEBUGARAN ATLET SEPAK BOLA - Alfiyana, Lana; Murbawani, Etisa Adi (Journal of Nutrition College, 2012)
Background: The athlete’s fitness is one of the supporting factor for athlete’s performance. Consumption of carbohydrate-electrolyte beverage during training  maintain hydration status and athlete’s performance. Coconut water is potential natural fluid that can be used as natural sport drink. Objective: The aim of this study was to verify the effect of additional sugar in coconut water on soccer athlete’s fitness Methode: An experimental study was done in randomized pretest - post test design with a control group. The subject were 18 soccer’s player aged 14-18 years at Persatuan Sepak Bola Kudus in August 2012. The control group is consumed pure coconut water and the treatment group is consumed coconut water which added with 3 g of sugar every 100 ml. The amount of fluid given based on fluid requirement during training. After physical training during 90minutes, all player completed the fitness test with cooper test 12 minutes run. Result: Consumption of coconut water affect the results of VO2 max on control group (p=0.016), and has no significant effect on treatment group (p=0,871). There no significant different between two groups in consumption of energy(p=0.643), fluid before training(p=0.385), body fat(p=0,698) and muscle mass(p=0.919) Conclusion: Consumption of pure coconut water affected on change value of VO2 max compared with coconut water which added with sugar